Cyber Weaponry Issues and Implications of Digital Arms (Advanced Sciences and Technologies for Security Applications, 2018)
There is little doubt that cyber-space has become the battle space for confrontations. However, to conduct cyber operations, a new armory of weapons needs to be employed. No matter how many, or how sophisticated an aggressor's kinetic weapons are, they are useless in cyber-space. This book looks at the milieu of the cyber weapons industry, as well as the belligerents who use cyber weapons. It discusses what distinguishes these hardware devices and software programs from computer science in general. It does this by focusing on specific aspects of the topic-contextual issues of why cyber-space is the new battleground, defensive cyber weapons, offensive cyber weapons, dual-use weapons, and the implications these weapons systems have for practice. Contrary to popular opinion, the use of cyber weapons is not limited to nation states; though this is where the bulk of news reporting focuses. The reality is that there isn't a sector of the political-economy that is immune to cyber skirmishes. So, this book looks at cyber weapons not only by national security agencies and the military, but also by law enforcement, and the business sector-the latter includes administrations termed non-government organisations (NGOs). This book offers study material suitable for a wide-ranging audience-students, professionals, researchers, policy officers, and ICT specialists.